Improving Pancasila Education Learning Outcomes through Fun Learning Based on Wordwall at SDN 1 Pabedilankaler - Dewi, Mutiara Sri; Dianasari, Dianasari; Nurkholis, Nurkholis (FKIP - Universitas Riau, 2025)
This study was conducted due to the low learning outcomes of Pancasila Education among fifth-grade students at SDN 1 Pabedilankaler. The purpose of this study was to improve student learning outcomes through the application of the Fun Learning method with the assistance of Wordwall media. The study used Kurt Lewin's Classroom Action model, which includes the stages of planning, implementation, observation, and reflection, and was conducted in two cycles. Data collection techniques included observation, student response questionnaires, documentation, and learning achievement tests. The results of the study showed that the application of the Fun Learning method with the assistance of Wordwall media was effective in improving student learning outcomes. There was an increase in the number of students achieving mastery, increased active participation in learning activities, and many students gave positive feedback on the use of Wordwall media. Therefore, this method is recommended as an alternative for teachers to create a more enjoyable and meaningful learning environment.